Penggunaan Model Pembelajaran Kooperatif Tipe Jigsaw Berbantuan Media Socrative untuk Meningkatkan Hasil Belajar Kimia kelas X SMA - Budhiartini, Baiq Nely; Junaidi, Eka; Anwar, Yunita Arian Sani (Chemistry Education Practice, 2024)
This study aims to explain how the use of jigsaw type cooperative learning model assisted by socrative media can improve chemistry learning outcomes for class X SMA. The study conducted was  quasi experimental design. The samples were randomly selected (simple random sampling) while the sample was X MIPA 1 as controll class and X MIPA 3 as experimental class. The independent variables of this study were the use of  jigsaw type cooperative learning model assisted by socrative media in the experimental class and the use of  jigsaw type cooperative learning model in the control class. The dependent variable in this study is chemistry learning outcomes. The chemistry learning outcomes were carried out by the N-gain test with the result that the student of experimental class has the most N-gain value in effective category of 63,88% compared to the controll class of 17,14%. The data in this study were declared abnormal and homogenous. Then, the hypothesis was carried out with Mann-Withney and Wilcoxon test. The result of the hypothesis test is there is an influence of the application of jigsaw type cooperative learning model assisted by socrative media on chemistry learning outcomes in class of X SMA.